The diversity of modern forms of preservation of rural and small towns’ wooden architecture in Poland - Szot-Radziszewska, Elżbieta (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
In this paper I discuss the modern forms of preservation of wooden historical monuments, included in the legal framework, such as protection via an entry in the records or monuments’ list, protection in open-air museum, being declared historical monument, protection via creation of a cultural park. I am pointing out the tragic state of the protection and conservation of the resources of this part of heritage. I discuss in wider scope the idea of open-air museum in Poland and the specificity of preservation of wooden monuments in the open-air museums as being the most rational and effective so far. I show positive protection examples via making use of and adaptation of the monument to the new function- cultural, educational or museum. I also emphasize the role of education and society participation in the protection of rural architecture. The wooden architecture is only 11% of all monuments registered in monuments’ list. In this situation, according to Polish law, the vast majority of monuments, not mentioned in the registry, cannot be protected. It is necessary to quickly create comprehensive regulatory framework and take action in the field of identification and inventory of wooden architecture as well as creating effective preservation programs. There is a chance to preserve the significant part of heritage by further diversification of forms of protection and adaptation in cooperation and substantive assistance of conservation department and museums as well as financial support of the governments. I present specific proposals of solutions to this problem.